Youth, gender and religion: The role of the Catholic Church in youth formation (Research, Society and Development, 2019)
The history of Brazil is deeply marked by the presence of the Catholic Church, brought by the Portuguese crown in the process of colonization was in charge of the educational formation of the population and consequently the moral and ideological formation. In recent decades the Church has focused more on young audiences through contemporary movements and group formation. From this finding, we aim to study the presence and influence of the Catholic Church in the construction and reproduction of discourses regarding the social roles of men and women with the youth. Our methodological path was through the review of texts that address the theme religion, Catholic Church, Youth and reading the discourses of Catholic leaders. From the analysis of these discourses, we found that religious movements that have a significant participation of young people, despite presenting a new guise, adopt retrogressive and conservative content. In this sense, we conclude that these movements reinforce the conceptions about the social roles of being male and female, in the religious field and in the public sphere.